Nuclear engineering handbook - Kok, Kenneth D (CRC, 2013)
Offering an overview of the field, this book provides an introduction to basic nuclear power and nuclear engineering development. Providing a historical review of nuclear reactors, it examines changes in technology and explores future directions. It describes various aspects of the nuclear fuel cycle.